Extracorporeal shock wave therapy for treating dyspareunia: A prospective, randomized, double-blind, placebo-controlled study - Hurt, Karel; Zahalka, Frantisek; Halaska, Michael; Rakovicova, Ivana; Rakovic, Jakub; Cmelinsky, Vaclav (Annals of physical and rehabilitation medicine, 2021)
BACKGROUND: Dyspareunia is a genital pain during or after penile-vaginal sexual intercourse. It is a painful spasm of the pelvic muscles that partly or entirely disables vaginal penetration. OBJECTIVES: We examined the effect of extracorporeal shock wave therapy (ESWT) on idiopathic non-organic dyspareunia in women. A prospective, randomized, double-blind, placebo-controlled study was conducted. METHODS: The study included 62 women who reported dyspareunia. Patients in the treatment and placebo groups received ESWT perineally weekly for 4 consecutive weeks; placebo patients received placebo stand-off treatment. The grade of dyspareunia was estimated by using the Marinoff Dyspareunia Scale and subjective pain intensity on a visual analog scale (VAS) before and after treatment. Follow-ups were conducted 1, 4 and 12 weeks after the final ESWT session. RESULTS: The study included 61 women. The treatment but not placebo group differed by the Marinoff Dyspareunia Scale and VAS. Differences before and after treatment within groups were all P<0.001 and between groups, P<0.001. Pain reduction was always>30%. The effect sizes were both large: Marinoff 0.825 and VAS 0.883. CONCLUSIONS: ESWT significantly reduced subjective pain in our women treated for dyspareunia.
Keywords: dyspareunie; lidé; Dyspareunia; Extracorporeal Shockwave Therapy; Female; prospektivní studie; léčba mimotělní rázovou vlnou; Prospective Studies; ženské pohlaví; Humans